The topography of the scalp-recorded visual N700 - Bender, Stephan; Oelkers-Ax, Rieke; Hellwig, Stefanie; Resch, Franz; Weisbrod, Matthias (Clinical neurophysiology, 2008)
Objective - To describe the topography of the N700 component of the scalp-recorded visual event-related potential (ERP) and to provide fundamental knowledge of the conditions under which it occurs. - Methods - We examined the time-course of visual ERP in response to the short (100ms) and prolonged (7s) presentation of simple salient visual stimuli separated by long interstimulus intervals employing high-resolution 64-channel DC-EEG. Current source density (CSD) mapping and spatio-temporal dipole source analysis were performed. - Results - CSD analysis revealed highly significant bilateral current sinks over occipito-temporal areas from about 450ms up to 1s after stimulus offset (visual N700). CSD topography and dipole source analysis suggested late prolonged activation of extrastriate visual areas which did not depend merely upon a stimulus offset response, afterimages or blinking, as confirmed by control conditions. - Conclusions - Our findings provide basic knowledge about the time-course of sensory activation. We found that passive watching of rare salient short stimuli automatically evoked sustained activity in the extrastriate visual cortex up to 1s after stimulus offset. - Significance - Visual N700 provides a promising tool for important insights into the cortical mechanisms of stimulus post-processing. Its role in associative learning of temporally non-overlapping stimuli (automatic ultra-short-term sensory memory) should be explored.
Available online 27 December 2007
Gesehen am 14.12.2021